The healthcare system in Poland and the basket of guaranteed healthcare services - Kaźmierczak, Daniel (Polish Journal of Public Health, 2009)
For many years the health care system in Poland has been struggling with same problems: poor funding of personnel, hospitals running into debts, limited access to medical services, long waiting lists, corruption and a decline in the value of the technical infrastructure. The main reason for this is the dissonance between the level of funds allocated to pay for medical services and the required volume of such services. The best solution to this situation (based on the experiences of other European countries) is to implement a package of guaranteed health care services.Successive governments have been working continuously on the creation of a package of health care services. Unfortunately, it should be noted, that this work depends to a large degree on political conditions, and the completion of many initiatives, founded on both theoretical and practical bases, is often impossible.The implementation of a new method of accounting for hospital use – Diagnosis Related Groups (JGP), which makes the registration and description of treatment processes possible both in the clinical sense and also in terms of cost categories, seems to be a good sign. It allows to determine the actual costs of medical procedures.The aim of this work is to show the progress of activities towards the implementation of a basket of guaranteed health care services in the Polish health care system, as well as to summarise the steps that have been taken as a part of this initiative.